The Role Of Motility And Gastric Acid Secretion in The Pathophysiology of Gastroesophageal Reflux Disease (GERD): A Literature Review - el mahroos, rifda (Journal of Diverse Medical Research : Medicosphere, 2025)
Introduction: Gastroesophageal reflux disease (GERD) is a chronic disorder of the upper gastrointestinal tract that involves a complex interaction between physiologic and pathologic factors. The two main components that play a role in this dynamic are gastric motility and acid secretion. Methods: This review used a narrative literature review approach by searching the current scientific literature from various databases between 2015-2024. Discussion: Normal gastric motility maintains gastric emptying efficiency and lowers the risk of reflux, while disorders such as delayed gastric emptying increase intragastric pressure and trigger reflux. Excessive secretion of gastric acid, especially HCl and pepsin, amplifies the aggressive nature of gastric contents and exacerbates damage to the esophageal mucosa. These two aspects interact to create an imbalance between protective and aggressive factors in GERD. Conclusion: The interplay between gastric motility and acid secretion plays a key role in the transition from physiologic to pathologic mechanisms in GERD, so a thorough understanding of both is important in diagnosis and treatment strategies.